Remote ischaemic conditioning in ST elevation myocardial infarction: a registry-based randomised trial. Issue 9 (20th August 2021) - Bainey, Kevin R; Zheng, Yinggan; Coulden, Richard; Sonnex, Emer; Thompson, Richard; Mei, Junyi; Bastiany, Alexandra; Welsh, Robert
Abstract : Objectives: Remote ischaemic conditioning (RIC) has been tested as a possible strategy for mitigating reperfusion injury in ST elevation myocardial infarction (STEMI) with primary percutaneous coronary intervention (PPCI). However, surrogate outcomes have shown inconsistent effects with lack of clinical correlation. Methods: We performed a registry-based randomised study of patients with STEMI allocated to RIC (4 cycles of blood pressure cuff inflation to 200 mm Hg for 5 min of ischaemia followed by 5 min of reperfusion) or standard of care (SOC) during PPCI. We examined the associations of RIC on core laboratory measurements of myocardial perfusion, infarct size (IS), left ventricular (LV) performance and clinical outcomes. Results: A total of 252 patients were enrolled. The median age was 61 (IQR: 55–70) years and 72.8% were male. Sum ST segment deviation resolution ≥50% was similar between RIC and SOC (65.2% vs 55.7%, p=0.269). In those with 3-day cardiovascular MRI (n=88), no difference in median (25th, 75th percentiles) IS (14.9% (4.5%, 23.1%) vs 16.1% (3.3%, 22.0%), p=0.980), LV dimensions (LV end-diastolic volume index: 78.7 (71.1, 91.2) mL/m 2 vs 79.9 (71.2, 88.8) mL/m 2, p=0.630; LV end-systolic volume index: 48.8 (35.7, 51.4) mL/m 2 vs 37.9 (31.8, 47.5) mL/m 2, p=0.551) or ejection fraction (50.0% (41.0%–55.0%) vs 50.0% (43.0%–56.0%), p=0.554) was demonstrated. Similar results were observed with 90-day cardiovascular MRI. At 1 year, the clinical composite of death, congestive heart failure, cardiogenic shock and recurrent myocardial infarction was similar in RIC and SOC (21.7% vs 13.3%, p=0.110). Conclusions: In a contemporary registry-based randomised study of patients with STEMI undergoing PPCI, adjunctive therapy with RIC did not improve myocardial perfusion, reduce IS or alter LV performance. Consequently, there was no difference in clinical outcomes within 1 year. Trial registration number: NCT03930589 .